Learning Independence Students - Widya Yolanda; Riska Ahmad (Jurnal Neo Konseling, 2019)
Learning independence is a learning activity carried out by someone with their freedom to determine and process their own teaching materials, time, place, utilizing learning resources that are started. In fact, there are still students who are not independent in learning. The purpose of this study is to describe the independence of students in terms of indicators: (1) personal autonomy, (2) self-management in learning, (3) achieving freedom to learn, and (4) directing oneself to organize material.This type of research is descriptive research. The population of the study was 738 students of SMP N 24 Padang with a sample of 259 students enrolled in the 2018/2019 school year. The instrument used in this study was a questionnaire. The data analysis technique used is the percentage technique The research findings revealed that the learning independence of students at SMP Negeri 24 Padang Padang, namely (1) personal autonomy was in the independent category with 53% (2) self-management in learning was in the very independent category with 48% (3) achieving freedom for degrees is in the independent category with 56% and (4) directing themselves to organizing material is in the independent category with 62% organizing material classified as independent. Based on these findings, it is expected that the BK teacher helps students in increasing student independence by providing information services, content mastery services and group guidance services with materials related to student learning independence.